Letter (copy) : Spanish Relief Fund - Parkin, E. G.
028-0182-001 EP/EK/67. Finance. 25th September, 1936. Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, France. Dear Mr. Stolz, SPANISH RELIEF FUND. I am forwarding herewith a bank receipt in respect of a further credit of £5,000 which we have placed to your deposit account, folio M.I.18.D. With beat wishes, Yours sincerely, Accountant. Bank Receipt. 292/946/28/182